The Strategic Role of Brand Equity and Customer Experience in Driving Promotional Success - Dina Lusianti; Ira Wakhidatin; Iwan Suroso (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the influence of brand image, brand quality, customer experience, and customer value on the success of sales promotions (a study on The Users Of The Originote in Kudus). The study population was consumers in Kudus who had received promotions for The Originote products. The sample consisted of 150 respondents selected using a purposive sampling technique. Instrument testing used validity and reliability tests, while data analysis used multiple linear regression with SPSS version 26. The results showed that brand image, brand quality, customer experience, and customer value each had a positive and significant effect on the sales promotion success. Simultaneously, these four variables also had a positive and significant effect on the success of The Originote sales promotions in Kudus.